2012
DOI: 10.1021/bi3015086
|View full text |Cite
|
Sign up to set email alerts
|

The Lipid Dependence of Antimicrobial Peptide Activity Is an Unreliable Experimental Test for Different Pore Models

Abstract: The role played by glutathione transferase P1-1 (GSTP1-1) in modulating the c-Jun N-terminal kinase (JNK) pathway has been extensively investigated using JNK isoforms known to exert opposite effects in the cells. We have expressed isoform JNK1α2, which has been reported to transmit a pro-apoptotic signal, and we have analyzed both the phosphorylation level and the activity of this kinase in the presence of GSTP1-1. Contrary to what previous studies suggest, we found that GSTP1-1 is able to form a complex with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…For instance, it is possible to determine peptide conformation, aggregation state, depth of insertion, orientation in the membrane and distribution between the two leaflets of the bilayer. Studies from our group have demonstrated that many of these phenomena modulate the final peptide membrane‐perturbing activity: peptide aggregation in water can compete with membrane binding and modulate peptide activity and selectivity; conformational equilibria can modulate the effective peptide hydrophobicity and therefore its tendency to associate to different membranes; peptide orientation and aggregation in the bilayer determine the structure of the pores …”
Section: The Physicochemical Approach: Vesicle Leakage and Water‐membmentioning
confidence: 99%
“…For instance, it is possible to determine peptide conformation, aggregation state, depth of insertion, orientation in the membrane and distribution between the two leaflets of the bilayer. Studies from our group have demonstrated that many of these phenomena modulate the final peptide membrane‐perturbing activity: peptide aggregation in water can compete with membrane binding and modulate peptide activity and selectivity; conformational equilibria can modulate the effective peptide hydrophobicity and therefore its tendency to associate to different membranes; peptide orientation and aggregation in the bilayer determine the structure of the pores …”
Section: The Physicochemical Approach: Vesicle Leakage and Water‐membmentioning
confidence: 99%
“…This has led to the proposal of a new interfacial model for AMP action (Wimley, 2010;Marks et al, 2011), which is a hybrid between the classical carpet model and the more recent toroidal model. The interfacial model consists of three main processes that take place consecutively: (i) an initial electrostatic interaction with the negatively charged bacterial membrane driven by the polar face; (ii) an interaction with the membrane hydrophobic core driven by the peptide hydrophobic face, causing the peptide to insert into the membrane, and (iii) the polar pocket interacts with the phospholipid head groups on the inner membrane leaflet causing negative curvature of this inner membrane (Marks et al, 2011;Bobone et al, 2012).…”
Section: Speculations On the Mechanism Of Action Of Scorpion Ampsmentioning
confidence: 99%
“…Whether one is a philosophical hunter or gatherer, it cannot be contested that a more detailed biophysical approach to understanding the mechanisms of action of these new peptides is essential if they are to have a positive impact on the clinical management of infection. Techniques such as NMR (Nomura et al, 2004(Nomura et al, , 2005, atomic force microscopy (AFM) (Garcia-Sa ez, 2007;Fernandez et al, 2012;Lam et al, 2012), secondary ionisation mass spectrometry (SIMS) (Rakowska et al, 2013) and X-ray photoemission electron microscopy (Won et al, 2011) can enable us to re-examine and refine our present interpretations of models of peptide interaction with microbial membranes (Bobone et al, 2012;Marks et al, 2011). Such experimental methods, taken together with molecular techniques to determine potential intracellular targets (e.g.…”
Section: Conclusion: Gatherers or Hunters?-lessons For The 21st Centurymentioning
confidence: 99%
“…Apparently, the fine details of the membrane-peptide interaction are dependent upon the specifics of both players of the association, as while magainin, a frog skin AMP, lies in the plane of the bi-layer; M2 delta, a helical segment of the nicotinic acetylcholine receptor, spans the membrane, perpendicular to the bi-layer plane [13]. It slowly became clear that the biophysical assumptions of neither of the two main membrane-perturbing models (barrel-stave and Shai-Matsuzaki-Huang carpet) are reliable for reaching structure-function conclusions [14]. The last push for alternative modes of action came after the observations that many AMPs fail to modulate membrane permeability at their microbiologically active concentration [15].…”
Section: Introductionmentioning
confidence: 99%